Evaluation of the effectiveness of hyaluronic acid viscosupplementation in the treatment of knee osteoarthritis - a narrative review of the current literature - Kość, Kacper; Muzyka, Natalia; Bukwald, Weronika; Panek, Gabriela; Abramowicz, Amanda; Rumin, Magdalena; Piliński, Remigiusz; Giersz, Jakub; Prusek, Adam; Gosztyła, Dominika (Quality in Sport, 2026)
Background: Knee osteoarthritis (OA) is a leading cause of global disability. This narrative review systematically evaluates the effectiveness of intra-articular hyaluronic acid (IAHA) viscosupplementation. The analysis assesses clinical efficacy, durability, safety, biomechanical and biological mechanisms, patient prognostic factors, and advanced formulations (tribosupplementation). Methods: A comprehensive literature search (PubMed/MEDLINE, Scopus, Google Scholar) up to 2026 was conducted, including systematic reviews, randomized controlled trials (RCTs), meta-analyses, and biomechanical studies. Clinical outcomes were primarily assessed using VAS and WOMAC scores. Results: IAHA provides moderate, highly durable pain and functional improvements. While intra-articular corticosteroids offer superior short-term analgesia (up to 4 weeks), IAHA demonstrates significantly greater sustained efficacy in the medium-to-long term (up to 6 months). Cross-linked HA enables effective single-injection regimens. Efficacy relies heavily on patient phenotype, with optimal results in non-obese patients having early-to-moderate OA (Kellgren-Lawrence grades I-III). IAHA benefits stem predominantly from long-term biological processes and viscoinduction rather than simple mechanical lubrication. Advanced fluid additives (e.g., bottle-brush polymers, hydrogels) represent a promising therapeutic future. Conclusions: IAHA is a highly effective and safe non-surgical OA treatment when guided by precision medicine and proper patient phenotyping. To maximize benefits and prevent dynamic joint overloading, HA injections must be strictly combined with targeted physical rehabilitation and gait retraining.